2015
DOI: 10.1007/s12011-015-0586-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum Trace Element Profiles, Prolactin, and Cortisol in Transient Ischemic Attack Patients

Abstract: The primary aim of the present study was to assess the association between trace element status, brain damage biomarkers, cortisol, and prolactin levels in transient ischemic attack (TIA) patients. Ten male and 10 female TIA patients were involved in this study. Age, gender, and BMI-matched volunteers served as the respective control group. Serum samples were examined for complement components C4 and C3a, vascular endothelial growth factor (VEGF), S100B, NR2 antibodies (NR2Ab), total antioxidant status (TAS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 52 publications
0
5
0
3
Order By: Relevance
“…There is increasing evidence that Pb toxicity is associated with increased oxidative stress due to ROS formation (reactive oxygen species), depletion of antioxidant capacity and increased lipid peroxidation [ 105 , 106 , 107 ]. Clinical research has revealed that high and low blood levels of Pb can adversely affect cardiovascular health, resulting in an increased risk of cardiovascular diseases, such as stroke [ 32 , 54 , 55 , 58 , 95 , 96 , 97 , 108 , 109 , 110 , 111 , 112 , 113 ]. In order to establish a link between trace elements and stroke, Medina Estévez et al [ 113 ] evaluated 45 elements and found that Pb was positively associated with ischemic stroke in both univariate and multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that Pb toxicity is associated with increased oxidative stress due to ROS formation (reactive oxygen species), depletion of antioxidant capacity and increased lipid peroxidation [ 105 , 106 , 107 ]. Clinical research has revealed that high and low blood levels of Pb can adversely affect cardiovascular health, resulting in an increased risk of cardiovascular diseases, such as stroke [ 32 , 54 , 55 , 58 , 95 , 96 , 97 , 108 , 109 , 110 , 111 , 112 , 113 ]. In order to establish a link between trace elements and stroke, Medina Estévez et al [ 113 ] evaluated 45 elements and found that Pb was positively associated with ischemic stroke in both univariate and multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In the cerebral ischemia model, PRL reduced the cerebral infarction area and cerebral water content and restored the physiological status ( 128 ). Transient ischemic attack increased PRL concentrations and increased plasma PRL levels were significantly linked with platelet P-selectin ( 129 , 130 ). Platelet surface P-selectin expression was associated with a worsening clinical course in acute ischemic stroke ( 131 ).…”
Section: Sex Hormones and Ischemic Strokementioning
confidence: 99%
“…According to the results of high-throughput profiling of the circulating proteome, there are significant sex-associated differences in GC signaling following IS ( O’Connell et al, 2018 ). In a cohort of patients with transient ischemic attacks (TIA), serum cortisol levels were significantly increased only in females ( Klimenko et al, 2016 ).…”
Section: Ischemic Stroke and Glucocorticoids: Clinical And Pre-clinical Datamentioning
confidence: 99%